Teacher-Parent Collaboration in Managing Hyperactive Children's Behaviors: A Case Study of Inclusive Early Childhood Education - Hariningsih, Hariningsih; Mahabbati, Aini (Papanda Publisher, 2025)
Managing hyperactive behaviors in inclusive early childhood settings requires coordinated efforts between educators and families to ensure optimal developmental outcomes. This qualitative case study examined teacher-parent collaboration strategies in addressing hyperactive children's problematic behaviors at an inclusive kindergarten in East Kutai Regency, Indonesia. Data were collected over four months through systematic observations, semi-structured interviews with teachers and parents, and document analysis. Participants included classroom teachers, special needs support staff, and parents of hyperactive children enrolled in class B1. Thematic analysis revealed three primary collaborative dimensions: behavioral recognition through structured communication protocols, participatory assessment procedures involving shared responsibility for instrument development and progress monitoring, and coordinated intervention implementation with regular feedback mechanisms. The findings demonstrate that effective collaboration requires systematic information exchange between home and school environments, with teachers sharing classroom observations while parents provide complementary insights about home-based behavioral patterns. Collaborative assessment procedures enabled comprehensive evaluation extending beyond limited school observation periods, with parents contributing to instrument design and participating in progress reviews. Intervention implementation was characterized by coordinated strategy application across both settings, supported by regular feedback exchanges and periodic evaluation meetings. Despite implementation challenges including time constraints and initial parental resistance to acknowledging children's special needs, the collaborative framework demonstrated effectiveness in managing hyperactive behaviors through sustained partnership efforts. The study contributes a practical model for inclusive early childhood programs, emphasizing the importance of structured collaboration protocols for supporting children with hyperactive behaviors. These findings have implications for educational policy development, teacher training programs, and family support services in inclusive educational settings.